A fully parameterized methodology for lattice materials with octahedron-based structures. Issue 10 (19th May 2021) - Zhu, Shaowei; Hu, Jiqiang; Wang, Bing; Ma, Li; Wang, Shixun; Wu, Linzhi
Abstract: We propose a methodology to parameterize lattice materials with octahedron-based structures. Transverse-isotropic octahedral repeatable-volume-elements (RVEs) with three mutually perpendicular planes are used to produce periodically arranged structures in 3D-space by translation. In this way, various lattice materials with octahedron-based structures can be generated by very simple RVE models. On this basis, the RVE is analyzed based on Timoshenko beam theory and predictive formulas for the effective Young's modulus and Poisson's ratio in all directions are obtained as the relationship of three types of parameters, i.e., slenderness ratio, lateral restraint ratio and strut angle. A comparison between the experimental and finite element results confirms that the formulas are feasible for both bending-dominated structures and stretching-dominated structures, and are precise than pervious formulas. Last, two examples of parameterization are given to verify the methodology is feasible for designing multi-layer lattice materials with the desired mechanical properties, especially with prescribed anisotropy.